1995
DOI: 10.1089/mdr.1995.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Antibiotic Resistance inHaemophilus influenzae

Abstract: During the last 10 years, a continuous increase in the incidence of beta-lactamase-producing Haemophilus influenzae has been observed; in addition, beta-lactamase-negative ampicillin-resistant strains are better identified and more frequently isolated. During the same period, resistance to tetracyclines and chloramphenicol decreased to a very low level. The incidence of resistant bacteria is highly variable according to the site of infection, patient's age, type of Haemophilus, and country or region, according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…According to the ampicillin breakpoint of Ն1 µg/ml, 44.4% of -lactamase non-producing H. influenzae strains were found to be intermediately resistant to ABPC. 16,17 The result of this study confirms the impression that -lactamase-negative, ampicillin-resistant (BLNAR) strains are increasingly prevalent among H. influenzae in Japan. 18 CDTR was active against H. influenzae, regardless of whether or not they producedlactamase, whereas CAM had a lower MIC than the breakpoint MIC in all strains.…”
Section: Susceptibility Testingsupporting
confidence: 74%
“…According to the ampicillin breakpoint of Ն1 µg/ml, 44.4% of -lactamase non-producing H. influenzae strains were found to be intermediately resistant to ABPC. 16,17 The result of this study confirms the impression that -lactamase-negative, ampicillin-resistant (BLNAR) strains are increasingly prevalent among H. influenzae in Japan. 18 CDTR was active against H. influenzae, regardless of whether or not they producedlactamase, whereas CAM had a lower MIC than the breakpoint MIC in all strains.…”
Section: Susceptibility Testingsupporting
confidence: 74%
“…In the light of the above data, the percentage of ␤-lactamase producers among Polish meningitis isolates is not very high, although it is three times higher than found among H. influenzae isolates responsible for lower respiratory tract infections in Poland (28). The observation that antibiotic resistance is more prevalent in encapsulated isolates, responsible for the majority of meningitis cases, than in nontypeable H. influenzae was also revealed by other authors (4,10,32). The results of some studies showed that there is also an increasing number of H. influenzae isolates resistant to chloramphenicol (e.g., Bangladesh, 21.5%; Paraguay, 20%; Cuba, 44%) and an increasing number of isolates resistant simultaneously to both mentioned antibiotics (2,26,31).…”
Section: Discussionmentioning
confidence: 51%
“…There is often an association between high frequencies of ß-lactamase and production of the type b capsule and isolated meningitis strains, especially among patients aged 6 months to 6 years (12,22). Our isolates showed a 95.9% frequency of type b strains and an 87.4% frequency of samples isolated from cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 55%